PERAN GURU DALAM PROSES PEMBELAJARAN SEBAGAI UPAYA PENINGKATAN SUMBER DAYA MANUSIA DI INDONESIA - Faqih Udin Zaini, Sandra Ameilia Salsabila, Nur Anggraeni Prahassetya, Perlita Dara Ayu, Milda (BASA Journal of Language & Literature, 2021)
Teachers are one example of a profession where they are tasked with teaching, educating, setting good examples and sharing knowledge with their students. Teachers are one of the most important components in efforts to improve human resources. The presence of a teacher figure who is able to change a person's personality, knowledge and insight. Making humans have a different sense of quality improvement in themselves, because not a few humans feel less confident in their abilities, so that way, this sense of improvement in themselves makes individuals more confident. Improving (HR) in Indonesia is also the government's concentration. This of course affects how to improve the quality of the education system, both curriculum, learning process and teachers as teachers. The quality of good teachers is of course believed to be able to encourage improvement (HR) in Indonesia. In order to achieve the desired goals, the role of teachers as the spearhead in achieving achievements and improving the quality of education is expected to be a success in increasing the quality of students who will become Indonesian Human Resources (HR).